The theory of punctuated equilibrium as an alternative research program to neo-Darwinism (Filosofia e História da Biologia, 2023)
The models of scientific change of the new philosophy of science (paradigms, research programs, research traditions) apply to study the history of biology and, more specifically, the development of the theory of evolution. After studying the two great traditions of research in biology (internalists or structuralists versus externalists or adaptationists) and noticing how specific research programs are developed within them (Cuvier versus Geoffroy), we study the emergence of Darwinism, within the adaptationist family, as a fuzzy research program in competition with other research programs (orthogenesis, Lamarckism). Then the source of the synthetic theory of evolution, its conversion into a paradigm, and the emergence of punctuated equilibrium as an alternative research program are studied. The main objective of the work is to show that the models of scientific change proposed by Larry Laudan, Thomas Kuhn and Imre Lakatos are not incompatible with each other and that they can fit inside each other to improve the understanding of the different stages of the history of biology.